Flexibility of network materials and the Rigid Unit Mode model: a personal perspective. (15th July 2019) - Dove, Martin T.
Abstract : The Rigid Unit Mode model was initially developed to understand the origin of displacive phase transitions in network silicate structures. Here, we review the successes of the model, and consider how it might apply to a wider range of network structures. This article is part of the theme issue 'Mineralomimesis: natural and synthetic frameworks in science and technology'.